2015
DOI: 10.3174/ajnr.a4359
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 4D DSA with 2D and 3D DSA in the Analysis of Normal Vascular Structures in a Canine Model

Abstract: BACKGROUND AND PURPOSE: 4D DSA allows viewing of 3D DSA as a series of time-resolved volumes of a contrast bolus. There is no comparison of the accuracy of the anatomic information provided by 4D DSA with that available from conventional 2D and 3D DSA. Our purpose was to make this comparison by using a canine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The 4D DSA reconstructions were performed at the research workstation using a two-step process that has been reported in previous studies 3 4. A conventional 3D DSA volume was reconstructed by using a reconstruction algorithm as implemented in the product and the same reconstruction parameters used for standard 3D DSA scans described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4D DSA reconstructions were performed at the research workstation using a two-step process that has been reported in previous studies 3 4. A conventional 3D DSA volume was reconstructed by using a reconstruction algorithm as implemented in the product and the same reconstruction parameters used for standard 3D DSA scans described above.…”
Section: Methodsmentioning
confidence: 99%
“…A conventional 3D DSA volume was reconstructed by using a reconstruction algorithm as implemented in the product and the same reconstruction parameters used for standard 3D DSA scans described above. In a next step, the temporal information contained in the rotational projection sequence was encoded into the constraint volume for every projection image,3 4 resulting in a temporal volumetric representation of the contrast flow through the subject's vasculature at the frame rate of the rotational projection image acquisition (up to 30 frames/s) 3 4. Time-resolved analysis of the whole volume or of cross-sectional views with slice thicknesses between 3 and 28 mm used VRT image representation with a pre-specified display in an unshaded mode.…”
Section: Methodsmentioning
confidence: 99%
“…The finding that A MCA was not significantly higher in AVM groups than in the control group was probably due to the inherently smaller oscillation range of waveforms in the distal arteries (MCA) than in the proximal arteries (ICA) in both groups. Compared with extradural VOIs, intradural VOIs have a lower SNR in t-RA and therefore produce less evident oscillation in the TDC 15. On the other hand, very large AVMs recruited more high-blood-flow feeders and our current protocols with 35 mL contrast could not produce satisfactory imaging owing to large non-iodinated inflows, leading to low SNR imaging and poor TDC waveform.…”
Section: Discussionmentioning
confidence: 89%
“…Time-resolved rotational angiography (t-RA) is a new technique which provides submillimeter spatial resolution and 40 millisecond temporal resolution for complex angioarchitecture. The radiation dose of t-RA was estimated to be 240% of that of conventional rotational angiography 15. It can improve the safety of endovascular treatment by providing real-time, phase-dependent, detailed anatomic structure.…”
Section: Introductionmentioning
confidence: 99%
“…17 An animal study based on a canine model also demonstrated that 4D-DSA is capable of delineating vasculature effectively. 18 Small-series studies also suggested that 4D-DSA enhances the ability to visualize the vascular anatomy of an AVM. 19,20 Accordingly, 4D-DSA enables evaluating feeding arteries, nidi, and draining veins in sequential imaging in 3D and eliminates the issue of overlapped vasculatures.…”
mentioning
confidence: 99%